Combined Replenishment of miR‐34a and let‐7b by Targeted Nanoparticles Inhibits Tumor Growth in Neuroblastoma Preclinical Models. Issue 20 (22nd April 2020) - Di Paolo, Daniela; Pastorino, Fabio; Brignole, Chiara; Corrias, Maria Valeria; Emionite, Laura; Cilli, Michele; Tamma, Roberto; Priddy, Leslie; Amaro, Adriana; Ferrari, Davide; Marotta, Roberto; Ferretti, Elisa; et al.
Abstract: Neuroblastoma (NB) tumor substantially contributes to childhood cancer mortality. The design of novel drugs targeted to specific molecular alterations becomes mandatory, especially for high‐risk patients burdened by chemoresistant relapse. The dysregulated expression of MYCN, ALK, and LIN28B and the diminished levels of miR‐34a and let‐7b are oncogenic in NB. Due to the ability of miRNA‐mimics to recover the tumor suppression functions of miRNAs underexpressed into cancer cells, safe and efficient nanocarriers selectively targeted to NB cells and tested in clinically relevant mouse models are developed. The technology exploits the nucleic acids negative charges to build coated‐cationic liposomes, then functionalized with antibodies against GD2 receptor. The replenishment of miR‐34a and let‐7b by NB‐targeted nanoparticles, individually and more powerfully in combination, significantly reduces cell division, proliferation, neoangiogenesis, tumor growth and burden, and induces apoptosis in orthotopic xenografts and improves mice survival in pseudometastatic models. These functional effects highlight a cooperative down‐modulation of MYCN and its down‐stream targets, ALK and LIN28B, exerted by miR‐34a and let‐7b that reactivate regulatory networks leading to a favorable therapeutic response. These findings demonstrate a promising therapeutic efficacy of miR‐34a and let‐7b combined replacement and support its clinical application as adjuvant therapy for high‐risk NB patients. Abstract : Targeted nanocarriers entrapping microRNAs (miRNA)‐mimics are selectively delivered to neuroblastoma cells. The technology exploits the nucleic acids negative charges to build coated cationic liposomes, which are functionalized with antibodies against GD2 receptor. The combined replenishment of miR‐34a and let‐7b by neuroblastoma‐targeted nanoparticles exerts a cooperative down‐modulation of key oncogenes. The reactivated regulatory networks lead to a favorable therapeutic response in preclinical models.